Effectiveness of an educational intervention to improve coping strategy and quality of life among primary caregivers of Jordanian women with breast cancer - Lee, Khuan; Mohd Nazan, Ahmad Iqmer Nashriq; Lim, Poh Ying; Mohammad Suliman; R. N., Jawad Obaidi (Zhongguo xun zheng yi xue za zhi bian ji bu, West China school of medicine, 2024)
BC is a significant health issue that affects individuals regardless of culture, race, gender, and economic and social status. The impact of BC is not only limited to the quality of life (QOL) and coping strategies among women but also their primary Caregivers (PCs). The care of women with BC includes physical, psychological, social, and environmental aspects and their ability to utilize positive coping strategies, i.e., problem- and emotion-focused strategies. Studies have demonstrated that the psychosocial well-being of PCs of patients undergoing care and treatment for BC in Jordan has received a limited amount of attention. Even though this group of people is confronted with psychological challenges, there are no interventions in place to cater to their requirements. This study aims to develop, implement, and evaluate the effectiveness of an educational intervention to improve coping strategies and QOL among PC for BC women in Jordan. The study methodology employed a quantitative and descriptive approach to investigate the connections between the dependent variables, namely coping strategies and QOL, and the independent factors, which encompass demographics and caregiving burden. The study was a randomized controlled trial with two arms: the control group, which received standard treatment alone, and the intervention group, which received an intervention program in addition to standard care. The intervention was implemented to assess its impact. Multiple variables were analyzed during three distinct periods. The study was conducted in selected public hospitals of Jordon. A prior power analysis was performed to determine the sample size based on a comparative study. A total of 31 primary PCs were selected from each hospital using inclusion eligibility, totaling 124.Data were collected in three phases: baseline, post-test, and 12-week follow-up. The multi-teaching topics covered in the educational intervention were introduction and information about BC and assisting the participants in adjusting to being a primary caregiver, problem-focused strategy, emotion-focused strategy, and QOL domains and practical care. The sessions were held on a single day and lasted between 30 and 70 minutes. SPSS version 23.0 was used to analyze the data. Socio-demographic characteristics, overall QOL, and physical, psychological, social, and environmental domains did not differ significantly between the groups at baseline. However, post-intervention comparisons revealed a significant mean difference between intervention and control groups for overall quality of life. These findings reflect the effectiveness of an educational intervention utilizing multi-teaching strategies and comprehensive components in improving QOL and coping strategies among PC for women with BC in Jordan. Policymakers could utilize and implement the low-cost educational intervention with significant effects on the QOL and coping strategies among PC in public hospitals in Jordan. The provision of intervention programs for PC necessitates additional research to develop programs and services that are contextually specific and will improve the QOL of PCs. It is important to provide suitable supportive interventions to assist the immediate family members of BC patients to lessen the strain on PCs. Key stakeholders in the healthcare industry, particularly in palliative care, should actively advocate for increased awareness of the needs of PCs. Additional research is needed to provide intervention programs and services tailored to the individual needs of PCs, to enhance their QOL.